Genetic Association of Drug Response to Erlotinib in Chinese Advanced Non-small Cell Lung Cancer Patients - Wang, Cong; Chen, Fang; Liu, Yichen; Xu, Qingqing; Guo, Liang; Zhang, Xiaoqing; Ruan, Yunfeng; Shi, Ye; Shen, Lu; Li, Mo; Du, Huihui; Sun, Xiaofang; et al. (Frontiers in Pharmacology, 2018)
The efficacy of erlotinib treatment for advanced non-small cell lung cancer (NSCLC) is due to its action as an epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI). Patients treated with erlotinib experience different drug responses. The effect of germline mutations on therapeutic responses and adverse drug responses (ADRs) to erlotinib in Chinese patients requires elucidation. Sixty Han Chinese advanced non-small cell lung cancer patients received erlotinib monotherapy and, for each participant, 76 candidate genes (related to EGFR signaling, drug metabolism and drug transport pathways) were sequenced and analyzed. The single-nucleotide polymorphisms (SNPs) rs1042640 in UGT1A10, rs1060463 and rs1064796 in CYP4F11, and rs2074900 in CYP4F2 were significantly associated with therapeutic responses to erlotinib. Rs1064796 in CYP4F11 and rs10045685 in UGT3A1 were significantly associated with adverse drug reaction. Moreover, analysis of a validation cohort confirmed the significant association between rs10045685 in UGT3A1 and erlotinib adverse drug response(unadjusted p = 0.015). This study provides comprehensive, systematic analyses of genetic variants associated with responses to erlotinib in Chinese advanced non-small cell lung cancer patients. Newly-identified SNPs may serve as promising markers to predict responses and safety in erlotinib-treated advanced non-small cell lung cancer patients after chemotherapy doublet.